Awakening and Recovery. Issue 2 (2nd April 2020) - McGee, Michael D.
ABSTRACT: Spiritual awakening promotes recovery from addiction. This review describes spirituality, the phenomenon of awakening, and the postulated mechanisms by which awakenings foster recovery. It then discusses the literature on spirituality and recovery. It concludes with a description of clinical interventions that clinicians can employ to promote awakenings in their patients and thereby enhance treatment outcomes.